1988
DOI: 10.1108/eb022652
|View full text |Cite
|
Sign up to set email alerts
|

The information systems profession: myth or reality?

Abstract: Much of the prior research into information systems (IS) workers has assumed that they are professionals. In this paper we examine the characteristics of IS workers, IS work and the IS workplace, and suggest that this perspective is mistaken. Drawing on the sociological theory of professions as a reference discipline we contend that IS professionalism is an inappropriate categorization, and that such a portrayal limits our understanding of IS workers and their work.We argue in this paper that a more faithful a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 28 publications
0
40
0
Order By: Relevance
“…More recently, Wynekoop and Walz [78] compared personality characteristics of IT professionals to population norms and found that IT professionals were more ambitious, logical, and conservative. Research has found that members of the IT workforce possess unique attitudes, interests, sense of identity, and work consciousness [57].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Wynekoop and Walz [78] compared personality characteristics of IT professionals to population norms and found that IT professionals were more ambitious, logical, and conservative. Research has found that members of the IT workforce possess unique attitudes, interests, sense of identity, and work consciousness [57].…”
Section: Introductionmentioning
confidence: 99%
“…Because the people drawn to a particular career can exhibit certain behaviour (Orlikowski, 1988(Orlikowski, , 1989Pettigrew, 1973;Schein, 1996a, b;Simpson et al, 2001;Van Maanen & Barley, 1984;Winroth, 2002), it stands to reason that in the teaching of engineers an approach particular to engineers may be valid, especially as an individual's need for identity is strong (Giddens, 1991). This need for identity may be derived through occupation (Van Maanen & Barley, 1984), ownership of skill or knowledge (Pierce, Dirks, & Kostova, 2001) in light of a perceived competitive environment (Boyce, 1999).…”
Section: Philosophies On Learningmentioning
confidence: 97%
“…The debate in marketing research and other disciplines extends to methodological issues which reflect the dichotomy of quantitative (positivistic) vs. qualitative (relativistic) approaches (Coviello, 1999). For example, Hunt (1991, p.398) seems to promote the former orientation but is led to conclude that "no single philosophy dominates marketing", a conclusion supported by Orlikowski and Baroudi (1989) in their examination of 155 information systems research articles published from 1983 to 1988. This debate highlights two key issues.…”
Section: Limitations and Directionsmentioning
confidence: 99%